ӨСПИРИМЛЕР АРАСЫНДА СУИЦИДИАЛ ҲӘРЕКЕТЛЕРДИҢ СОЦИАЛ - ПСИХОЛОГИЯЛЫҚ ӨЗГЕШЕЛИКЛЕРИ - Сулетбаева, Э. (FAN va JAMIYAT, 2016)
The article deals with the information about the reasons of suicidal incidences among teenagers and the kinds of behavior (demonstrative, affective, true), including internal and external suicidal behavior. It is recommended to solve such problems by qualified personnel having necessary knowledge and working in the sphere of education system.